CD39 abrogates platelet-derived factors induced IL-1β expression in the human placenta - Forstner, Désirée; Guettler, Jacqueline; Brugger, Beatrice A.; Lyssy, Freya; Neuper, Lena; Daxboeck, Christine; Cvirn, Gerhard; Fuchs, Julia; Kraeker, Kristin; Frolova, Alina; Valdes, Daniela S.; Stern, Christina; et al. (Frontiers in Cell and Developmental Biology, 2023)
Tissue insults in response to inflammation, hypoxia and ischemia are accompanied by the release of ATP into the extracellular space. There, ATP modulates several pathological processes, including chemotaxis, inflammasome induction and platelet activation. ATP hydrolysis is significantly enhanced in human pregnancy, suggesting that increased conversion of extracellular ATP is an important anti-inflammatory process in preventing exaggerated inflammation, platelet activation and hemostasis in gestation. Extracellular ATP is converted into AMP, and subsequently into adenosine by the two major nucleotide-metabolizing enzymes CD39 and CD73. Here, we aimed to elucidate developmental changes of placental CD39 and CD73 over gestation, compared their expression in placental tissue from patients with preeclampsia and healthy controls, and analyzed their regulation in response to platelet-derived factors and different oxygen conditions in placental explants as well as the trophoblast cell line BeWo. Linear regression analysis showed a significant increase in placental CD39 expression, while at the same time CD73 levels declined at term of pregnancy. Neither maternal smoking during first trimester, fetal sex, maternal age, nor maternal BMI revealed any effects on placental CD39 and CD73 expression. Immunohistochemistry detected both, CD39 and CD73, predominantly in the syncytiotrophoblast layer. Placental CD39 and CD73 expression were significantly increased in pregnancies complicated with preeclampsia, when compared to controls. Cultivation of placental explants under different oxygen conditions had no effect on the ectonucleotidases, whereas presence of platelet releasate from pregnant women led to deregulated CD39 expression. Overexpression of recombinant human CD39 in BeWo cells decreased extracellular ATP levels after culture in presence of platelet-derived factors. Moreover, platelet-derived factors-induced upregulation of the pro-inflammatory cytokine, interleukin-1β, was abolished by CD39 overexpression. Our study suggests that placental CD39 is upregulated in preeclampsia, suggesting an increasing demand for extracellular ATP hydrolysis at the utero-placental interface. Increased placental CD39 in response to platelet-derived factors may lead to enhanced conversion of extracellular ATP levels, which in turn could represent an important anti-coagulant defense mechanism of the placenta.